Distinct mechanisms for distractor suppression and target facilitation - Noonan, M; Adamian, N; Pike, A; Printzlau, F; Crittenden, B; Stokes, M (Society for Neuroscience, 2016)
It is well established that preparatory attention improves processing of task-relevant stimuli. Although it is often more important to ignore task-irrelevant stimuli, comparatively little is known about preparatory attentional mechanisms for inhibiting expected distractions. Here, we establish that distractor inhibition is not under the same top-down control as target facilitation. Using a variant of the Posner paradigm, participants were cued to either the location of a target stimulus, the location of a distractor, or were provided no predictive information. In Experiment 1, we found that participants were able to use target-relevant cues to facilitate target processing in both blocked and flexible conditions, but distractor cueing was only effective in the blocked version of the task. In Experiment 2, we replicate these findings in a larger sample and leveraged the additional statistical power to perform individual differences analyses to tease apart potential underlying mechanisms. We found no evidence for a correlation between these two types of benefit, suggesting that flexible target cueing and distractor suppression depend on distinct cognitive mechanisms. In Experiment 3, we use EEG to show that preparatory distractor suppression is associated with a diminished P1, but we found no evidence to suggest that this effect was mediated by top-down control of oscillatory activity in the alpha band (8–12 Hz). We conclude that flexible top-down mechanisms of cognitive control are specialized for target-related attention, whereas distractor suppression only emerges when the predictive information can be derived directly from experience. This is consistent with a predictive coding model of expectation suppression.